Problematika dan Solusi Dalam Ekonomi Islam di Indonesia - Desi Nurhabibah; Sunarto (STIS DAFA MATARAM, 2024)
The purpose of this study is to determine what obstacles arise in the implementation of the sharia economic system in Indonesia, how problems arise and how to overcome them so that they can be resolved periodically. The research method used is descriptive research. The results of this study indicate that the solutions to overcome the problems of sharia economics in Indonesia include the correlation of educational institutions in the development of sharia-based concepts, government attention to the real role of sharia economics in the economy of the Indonesian people who are predominantly Muslim, the introduction of dinar and dirham currencies to enrich the nawacita and sharia economic transactions in society and expanding the network of sharia economics in Indonesia by adding competent human resources in each region with the aim of being able to provide understanding to the community who want to know the concept of sharia economics in Indonesia. The contributions to be achieved in this study include providing solutions to relevant stakeholders to implement solid and systematic regulations and not overlapping with other regulations between institutions, improving the quality of competent and professional human resources, training/education/socialization of employees and the community, innovative marketing, product innovation, adjustments to the actual sector, improving services and professionalism are needed in answering solutions to the sharia economy in Indonesia.